Unexpected results from direct measurement, with a torsion microbalance in a closed system, of calcification rates of the coral Agaricia agaricites (Scleractinia:Agariicidae) and concomitant changes in seawater pH - Sandeman, Ian M. (Revista de Biología Tropical, 2016)
Ocean acidification is impacting the calcification of corals, but the mechanisms of calcification are still unclear. To explore the relationship between calcification and pH, small pieces of coral were suspended from a torsion microbalance in gently stirred, temperature controlled, seawater in a closed chamber. Net calcification rate and pH were continuously monitored while light, temperature or pH could be manipulated. The coral pieces were from the edges of thin plates of Agaricia agaricites and were studied alive and freshly collected. Unexpectedly, when calcification was taking place (n=9, 0.082 mg.hr-1.cm-2), as determined by weight increase, the pH of the surrounding seawater medium changed little (n=10, -0.0047 pH units.hr-1.cm-2). When calcification was not taking place the decrease of seawater pH was an order of magnitude higher, -0.013 pH units.hr-1.cm-2. This is the opposite of what is expected when calcium carbonate (CaCO3) forms. Similarly, fresh skeleton initially showed no change of pH in the seawater medium although the rates of weight gain were high (upto 1.0 mg hr-1.cm-2). After 10 hours, as the rate of deposition decreased following a generalized Michaelis-Menten growth curve, the pH began to decrease dramatically indicating an increase of CO2 in the seawater. These unexpected results can be explained if unstable calcium bicarbonate (Ca(HCO3)2) is formed in the organic matrix/carbonic anhydrase surface and slowly transforms later to CaCO3. Pieces of living coral monitored in the chamber for 30 hours gained weight during the day and loss it at night. The loss would be consistent with the transformation of Ca(HCO3)2 to CaCO3 with the release of CO2. The mean calcification rate of live coral was greater (n=8, p=0.0027) in high light (120 μmol.s-1.m-2) at 0.098 mg.hr-1.cm-2, compared to 0.063 mg.hr-1.cm-2 in low light (12 μmol.s-1.m-2). However, at the same time the mean rate of pH change was -0.0076 under low light compared to -0.0030 under high light (n=8, p=0.0001). The difference can be ...